Zap70 Regulates TCR-Mediated Zip6 Activation at the Immunological Synapse - Kim, Bonah; Kim, Hee Young; Lee, Won-Woo (Frontiers in Immunology, 2021)
The essential microelement zinc plays immunoregulatory roles via its ability to influence signaling pathways. Zinc deficiency impairs overall immune function and resultantly increases susceptibility to infection. Thus, zinc is considered as an immune-boosting supplement for populations with hypozincemia at high-risk for infection. Besides its role as a structural cofactor of many proteins, zinc also acts as an intracellular messenger in immune cell signaling. T-cell activation instructs zinc influx from extracellular and subcellular sources through the Zip6 and Zip8 zinc transporters, respectively. Increased cytoplasmic zinc participates in the regulation of T-cell responses by modifying activation signaling. However, the mechanism underlying the activation-dependent movement of zinc ions by Zip transporters in T cells remains elusive. Here, we demonstrate that Zip6, one of the most abundantly expressed Zip transporters in T cells, is mainly localized to lipid rafts in human T cells and is recruited into the immunological synapse in response to TCR stimulation. This was demonstrated through confocal imaging of the interaction between CD4+ T cells and antigen-presenting cells. Further, immunoprecipitation assays show that TCR triggering induces tyrosine phosphorylation of Zip6, which has at least three putative tyrosine motifs in its long cytoplasmic region, and this phosphorylation is coupled with its physical interaction with Zap70. Silencing Zip6 reduces zinc influx from extracellular sources and suppresses T-cell responses, suggesting an interaction between Zip6-mediated zinc influx and TCR activation. These results provide new insights into the mechanism through which Zip6-mediated zinc influx occurs in a TCR activation-dependent manner in human CD4+ T cells.